Outcome of elderly patients with classical Hodgkin's lymphoma - Sykorova, A; Mocikova, H; Lukasova, M; Koren, J; Stepankova, P; Prochazka, V; Belada, D; Klaskova, K; Gaherova, L; Chroust, K; Buresova, L; Markova, J; et al. (Leukemia research, 2020)
INTRODUCTION: The optimal management of elderly patients (pts) with Hodgkin's lymphoma is not yet defined. The aims of the present study were: 1) to evaluate clinical and laboratory characteristics of elderly pts; 2) to indentify risk factors for unfavorable outcome. PATIENTS AND METHODS: The outcome of 182 pts ≥ 60 years (y) was retrospectively analyzed (median age, 67y). Mixed cellularity histology was diagnosed in 49.5 %, advanced stage of disease was in 68.7 % pts, CIRS > 3 in 35.7 %, ECOG PS ≥ 2 in 22.9 % (60-69y) of pts. Chemotherapy (CMT) alone was used in 69.2 % and combination of CMT and radiotherapy in 26.9 % of pts. Anthracycline-based CMT received 83.5 % of pts. The median follow-up was 4.5y. RESULTS: The overall response/complete remission rate was 85.6/70.7 %. The median progression free survival (PFS) and overall survival (OS) were 10y and 11.3y, respectively. Estimated 5-y PFS and 5-y OS were 65.7 % (in contrast to 98.2 % in pts < 60y; p < 0.001) and 70.5 % (99.4 % in pts < 60y; p < 0.001). Overall 70 (38.5 %) elderly pts died. The independent risk factors for a shorter OS included CIRS > 3, lymphopenia < 8 % and anthracycline-free CMT, for a shorter PFS anthracycline-free CMT and lymphopenia < 8 %. CONCLUSION: CIRS > 3, lymphopenia < 8 % and anthracycline-free chemotherapy appear to be significant for unfavorable outcome.
Keywords: senioři; Disease Management; senioři nad 80 let; Radiotherapy; Prognosis; Česká republika; výsledek terapie; Kaplan-Meier Estimate; Middle Aged; Chemotherapy; registrace; mužské pohlaví; Elderly population; ochrana veřejného zdraví; Kaplanův-Meierův odhad; Hodgkin’s lymphoma; Multimodal Imaging; Risk factors; Hodgkin Disease; Public Health Surveillance; management nemoci; Czech Republic; Registries; hodnocení výsledků zdravotní péče; Aged, 80 and over; ženské pohlaví; prognóza; Humans; Outcome Assessment, Health Care; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Hodgkinova nemoc; multimodální zobrazování; protokoly protinádorové kombinované chemoterapie; Female; Aged; Treatment Outcome; lidé; Male; Outcome